Analysis of the current situation regarding the impact of the daily schedule on the holistic development of preschoolers in early education institutions - Lilia CEBANU; Snejana COJOCARI-LUCHIAN (Acta et Commentationes, Sciences of Education, 2025)
The article highlights the importance of the daily schedule in supporting the holistic development of preschool children in kindergartens. A well-structured daily routine „contributes to the physical, cognitive, emotional, and social development of children”, serving as a key element in forming healthy habits and a balanced lifestyle. The study emphasizes that, although health education is included in kindergarten activities, the information provided to preschoolers is often limited, and educators do not feel sufficiently prepared to effectively address this area. The daily routine is organized to include educational activities, play, drawing, rest, meals, and outdoor time. In implementing this routine, educators most frequently use playful methods such as games, songs, and poems, followed by visual activities and, to a lesser extent, educational projects. The study’s conclusions highlight the need for continuous professional development of teachers in the field of health education and the adaptation of the daily routine to the real needs of children in order to support harmonious and responsible development. Health education, integrated into the daily routine, thus becomes an effective tool for promoting well-being among preschoolers.